Heterogeneous activation of peroxymonosulfate by Cu+-decorated g-C3N4 under sunlight for degradation of organic pollutants. Issue 6 (December 2021) - Yang, Linhai; Ren, Xuechang; Zhang, Yujie; Chen, Zuoyan
Abstract: This article is an in-depth study of the basis of Cu + -decorated triazine-based g-C3 N4 (Cu + /g-C3 N4 ) nanosheet-activated H2 O2 . In this study, peroxymonosulfate (PMS) was activated by Cu + /g-C3 N4 under sunlight and used to treat simulated wastewater RhB. The properties of g-C3 N4 and Cu + /g-C3 N4 were characterized by UV–Vis DRS and PL. The results indicated that the introduction of Cu + in g-C3 N4 can enhance the separation of photogenerated electron-hole pairs. The Cu + /g-C3 N4 (1:4) samples exhibited the best PMS activation performance under sunlight when 0.5 g/L catalyst dose and 0.5 mmol/L PMS concentration were used, and the removal rate of RhB reached 95.7% in 30 min. Moreover, better catalytic activity of the system can be achieved in the initial pH range of 2.0–10.0. The investigation results of the catalytic mechanisms showed that the prepared Cu + /g-C3 N4 catalyst constructs a dual reaction center of Cu + /Cu 2+ cycling and e CB − / h VB + transfer for efficient PMS activation. The degradation of pollutants benefits from the participation of a variety of free radicals, which are generated by sunlight-assisted heterogeneous activation of PMS. This study has resulted in substantial progress in activating multiple oxidants with a single heterogeneous catalyst and provides a feasible way to treat refractory wastewater using Cu + /g-C3 N4 with PMS under sunlight. Graphical Abstract: ga1 Highlights: Cu + -decorated g-C3 N4 nanosheet activation peroxymonosulfate. The high catalytic activity of this catalyst can be achieved at different initial pH in range of 2.0–10.0. Cu + /g-C3 N4 constructs a dual reaction center of the Cu + /Cu 2+ cycling and e CB − / h VB + transferring for PMS activation.